Shared decision making embedded in the undergraduate medical curriculum: A scoping review. - Marie-Anne Durand; Peter R DiMilia; Julia Song; Renata W Yen; Paul J Barr (PLoS ONE)
Objective Shared decision making (SDM) training is shown to be effective and is increasingly embedded in continuing medical education. There is little evidence, however, about undergraduate medical education for SDM. The aim of this scoping review was to identify existing SDM training embedded in the undergraduate medical curriculum and analyze their impact. Methods The authors systematically searched the extant literature for peer reviewed articles, hand searched key journals and reference lists of key articles, and contacted relevant stakeholders as part of a key informant analysis. Results Included in the qualitative synthesis were 12 studies evaluating 11 SDM courses in medical education across six countries. Most courses integrated SDM training in clinical clerkship and varied in length from one to seven hours. The majority of studies assessed course impact on students' skills in SDM. Most studies suggested that students' skills and confidence in SDM significantly increased post-training, but three studies reported no significant improvement in SDM. Ten courses continue to be taught routinely. Conclusion Overall, studies suggested a positive impact on medical students' skills, confidence, and attitudes regarding SDM. Embedding SDM training in undergraduate medical education may be a practical and effective solution for current barriers to the widespread adoption of SDM.